Failure to produce direct object clitic pronouns as a clinical marker of SLI in school-aged Italian speaking children. (September 2014) - Arosio, Fabrizio; Branchini, Chiara; Barbieri, Lina; Guasti, Maria Teresa
Abstract We administrated a clitic elicitation task to 16 school-aged Italian speaking children with specific language impairment (SLI) in order to investigated whether the failure to produce third person direct object clitics (DO clitics) is a persistent clinical marker of SLI in Italian; we examined whether this failure also extends to reflexive clitics. Results show that Italian children with SLI aged 6 to 9;11 years fail to produce DO clitics and tend to produce a lexical noun introduced by a determiner (full DP) in the argument postverbal position instead of the pronoun; the production of reflexive clitics is preserved in the same population. Receiver operating characteristic curve analyses and computation of likelihood ratios show that the failure to produce DO clitics is a persistent good clinical marker of SLI in Italian. We argue that DO clitic production requires complex morphosyntactic operations that are hardly achieved by children with SLI; our findings are compatible with theories considering SLI as a deficit of processing complex linguistic relations.